Study on rheological and micro-structural properties of different modified asphalt by using organic and inorganic modifier - Song Zhao; Haitao Zhang; Yuping Feng; Jingdi Li; Meiyi Gao; Guangyuan Wu (Case Studies in Construction Materials, 2023)
In order to evaluate the high and low temperature rheological properties of different modified asphalt, this paper prepared different types of modifiers and short-term aging modified asphalt (RTFOT), using dynamic shear rheometer (DSR) and bending beam rheological test (BBR) to compare and analyze the deformation resistance and stress sensitivity of different types (organic and inorganic) modified asphalt, determine its PG classification, and evaluate its fitting parameters with the help of Burgers model. The low-temperature mechanical properties of the fitting parameters were evaluated by the Burgers model; the chemical composition of different modified asphalts was analyzed by Fourier transform infrared spectroscopy (FTIR), and the microscopic state of the modified asphalts was observed by fluorescence microscopy. The results show that: with the increase of temperature, the high temperature deformation resistance of organic modified asphalt is better than that of inorganic modified asphalt, and PE modified asphalt is the best, and the low temperature performance of inorganic modified asphalt is poor, and the addition of SBS It will improve the low temperature crack resistance of asphalt. The road performance of different modified asphalts from strong to weak are PE modified asphalt, SBS modified asphalt, diatomite modified asphalt, montmorillonite modified asphalt. The research results have certain reference value for further research on different types (organic and inorganic) of modified asphalt.